Analisis Perbandingan Implementasi Kurikulum 2013 dan Kurikulum Merdeka di SD Negeri 6 Pangkalpinang - Silvia Dwi (Magister Pendidikan Agama Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The purpose of this research is to analyze the differences in curriculum structure, teaching and learning processes, and assessment of the 2013 Curriculum and Merdeka Curriculum at SD Negeri 6 Pangkalpinang. This research is field research with a qualitative descriptive research type. The research subjects were the principal, teachers, and students of SD Negeri 6 Pangkalpinang. The data used by researchers are primary and secondary. The methods used in data collection are observation, interview, and documentation. In this study, researchers used the Miles and Huberman model data analysis procedure. The data obtained were analyzed through the stages of data reduction, data presentation, and verification. Based on the research, it is concluded that (a) the structure of the 2013 Curriculum and the Merdeka Curriculum at SD Negeri 6 Pangkalpinang has differences in terms of lesson hours, hour-setting policies, and subject groupings. In addition, the basic competencies in the 2013 Curriculum are quite dense, covering the basic competencies for knowledge and skills with themes that have been determined by the government. Meanwhile, the subject matter in the Merdeka Curriculum is essential material, with a more flexible allocation of hours arranged by the school. (b) The teaching and learning process in the 2013 Curriculum and the Merdeka Curriculum at SD Negeri 6 Pangkalpinang has differences. The 2013 Curriculum is implemented thematically with an assessment per lesson, while the Merdeka Curriculum is implemented with a subject approach. The learning methods and media used are quite varied, both in the 2013 Curriculum and the Merdeka Curriculum. (c) Assessment in the 2013 Curriculum and Merdeka Curriculum at SD Negeri 6 Pangkalpinang has differences. The 2013 Curriculum uses minimum completion criteria with the principle of completeness in learning where aspects of attitude, knowledge, and skills are differentiated in assessment. Meanwhile, the Merdeka Curriculum uses the criteria for achieving learning objectives with a differentiation strategy based on a combined assessment of attitudes, knowledge, and skills. In the 2013 Curriculum, there is one report card containing attitudes, knowledge, and skills, while in the Merdeka Curriculum, there are two report cards, namely the lesson value report card, which is a combination of attitude, knowledge, and skills values and the project report card for strengthening the Pancasila student profile